2020
DOI: 10.3389/fimmu.2020.00076
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal IgM Antibodies Targeting Candida albicans Hyr1 Provide Cross-Kingdom Protection Against Gram-Negative Bacteria

Abstract: Recent years have seen an unprecedented rise in the incidence of multidrug-resistant (MDR) Gram-negative bacteria (GNBs) such as Acinetobacter and Klebsiella species. In view of the shortage of novel drugs in the pipeline, alternative strategies to prevent, and treat infections by GNBs are urgently needed. Previously, we have reported that the Candida albicans hypha-regulated protein Hyr1 shares striking three-dimensional structural homology with cell surface proteins of Acinetobacter baumannii. Moreover, acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Therefore, studies focusing on understanding the role of humoral immunity during viral and fungal coinfections are scarce. Of note, monoclonal antibodies targeting Candida albicans can confer protection against lethal pulmonary infections by Gram-negative bacteria in mice ( 486 ), while Pneumocystis infection can protect mice against subsequent influenza infection due to the enhancement of the influenza virus-specific antibody response ( 487 ). Susceptibility mechanisms could include the activation of low-affinity cellular responses and/or production of nonneutralizing antibodies that could facilitate coinfections ( 488 490 ).…”
Section: Copathogenesis Of Respiratory Viral-fungal Coinfectionsmentioning
confidence: 99%
“…Therefore, studies focusing on understanding the role of humoral immunity during viral and fungal coinfections are scarce. Of note, monoclonal antibodies targeting Candida albicans can confer protection against lethal pulmonary infections by Gram-negative bacteria in mice ( 486 ), while Pneumocystis infection can protect mice against subsequent influenza infection due to the enhancement of the influenza virus-specific antibody response ( 487 ). Susceptibility mechanisms could include the activation of low-affinity cellular responses and/or production of nonneutralizing antibodies that could facilitate coinfections ( 488 490 ).…”
Section: Copathogenesis Of Respiratory Viral-fungal Coinfectionsmentioning
confidence: 99%
“…Panobacumab and AR-105 target polysaccharides produced by P. aeruginosa and are under investigation as adjuncts with standard-of-care antibiotics for nosocomial P. aeruginosa infections [ 95 , 96 ]. Continued advancements in molecular modelling and bioinformatics are likely to yield additional targets for pathogens associated with MDR Gram-negative respiratory infections [ 97 ].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…A study by Youssef et al. identified a Hyrl antigen specific IgM antibody from a fungal infection, Candida albicans , that was able to cross-react with two Gram-negative bacteria, Acinetobacter baumannii and Klebsiella pneumoniae ( 11 ). The study found there was structural homology between the hypha-regulated protein (Hyr1) of C. albicans and the cell surface protein of A. baumannii.…”
Section: Introductionmentioning
confidence: 99%
“…The study found there was structural homology between the hypha-regulated protein (Hyr1) of C. albicans and the cell surface protein of A. baumannii. Furthermore, the study found that active vaccination with Hyr1p-N protein or passive immunization with the IgM antibody to that protein protects mice from A. baumannii infections and prevents severe bacteremia ( 11 ). This IgM antibody illustrates a cross-kingdom humoral response that is not only capable of cross-reacting with both a bacterial and fungal protein, but is also functionally protective against A. baumannii infections and their pathologies.…”
Section: Introductionmentioning
confidence: 99%